2012
DOI: 10.1371/journal.pone.0042913
|View full text |Cite|
|
Sign up to set email alerts
|

Rapamycin Inhibits Proliferation of Hemangioma Endothelial Cells by Reducing HIF-1-Dependent Expression of VEGF

Abstract: Hemangiomas are tumors formed by hyper-proliferation of vascular endothelial cells. This is caused by elevated vascular endothelial growth factor (VEGF) signaling through VEGF receptor 2 (VEGFR2). Here we show that elevated VEGF levels produced by hemangioma endothelial cells are reduced by the mTOR inhibitor rapamycin. mTOR activates p70S6K, which controls translation of mRNA to generate proteins such as hypoxia inducible factor-1 (HIF-1). VEGF is a known HIF-1 target gene, and our data show that VEGF levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 21 publications
4
58
1
Order By: Relevance
“…Many studies have shown that knocking down the expression of HIF-1α could significantly control the tumor growth, inhibit angiogenesis and invasion (29,32,33), so we focused our study on HIF-1α. To date it has been shown that multiple signaling pathways are involved in the regulation of hypoxia-induced HIF-1α protein stabilization and expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that knocking down the expression of HIF-1α could significantly control the tumor growth, inhibit angiogenesis and invasion (29,32,33), so we focused our study on HIF-1α. To date it has been shown that multiple signaling pathways are involved in the regulation of hypoxia-induced HIF-1α protein stabilization and expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypoxia also regulates the function of endothelial cells through the VEGFR2/HIF-1 pathway, which is also a classical pathway for endothelial angiogenesis (29,30). As shown in Fig.…”
Section: F2 Inhibits Tumor Angiogenesis In Vitromentioning
confidence: 99%
“…The overactivation of the PI3K/Akt/mTOR pathway, a signaling pathway that plays a key role in cellular growth and survival, has been implicated in various tumor pathogeneses, and as such, the inhibition of the PI3K/Akt/mTOR pathway is of therapeutic interest [112][113][114]. Medici and Olsen [39] found that HemECs had constitutively active PI3K/Akt/ mTOR/p70S6K and tested their hypothesis that these cells could be sensitive to mTOR inhibitors (e.g., rapamycin). Finally, they demonstrated that the treatment of HemECs with rapamycin results in a significant decrease in HIF-1 and VEGF-A levels and in reduced proliferation.…”
Section: Hif-α-mediated Pathwaymentioning
confidence: 99%
“…27 The drug also reduces the proliferation of hemangioma EC, as well as VEGF and hypoxia-inducible factor-1a levels in these cells. 26 Rapamycin, however, is a potent immunosuppressant, and the long-term effects of systemic drug exposure would be deemed deleterious in individuals with a normal immune system. To investigate the potential clinical utility of topically applied rapamycin in localized cutaneous vascular tumors, we have developed a rapamycin cream that inhibited mTOR signaling and the growth of vascular tumors in mice.…”
Section: Rapamycin Delivered Systemically or Topically Reduces The mentioning
confidence: 99%
“…It suppresses the self-renewal and vascular differentiation potential of infantile hemangioma stem cells, and reduces VEGF and hypoxia-inducible factor-1a levels in hemangioma EC. 26,27 Rapamycin and rapalogs have shown promising results in clinical trials for other types of vascular lesions, including Kaposi's sarcoma, kidney angiomyolipoma and complicated vascular anomalies. 17,28,29 As rapamycin is an immunosuppressive drug, it can cause significant negative side effects in healthy individuals when taken systemically.…”
mentioning
confidence: 99%